Characterization of Surface Fatigue Crack Nucleation and Microstructurally Small Crack Growth in High Strength Aluminum Alloys - Fleishel, Robert; Cauthen, Cole; Daniewicz, Steven; Baker, Andrew; Jordon, J. Brian; TerMaath, Stephanie (Frontiers in Materials, 2021)
It is well established that fatigue crack nucleation and small crack growth in high strength aluminum alloys are highly influenced by the surrounding microstructure including grain boundaries, texture, inclusion barriers, among other factors. As such, specific and targeted experimental and computational methods are necessary to accurately capture and predict the discrete behavior of microstructurally small fatigue cracks. In this study, surface fatigue crack nucleation and microstructurally small crack growth in high strength aluminum alloys, commonly used in aerospace applications, is evaluated through a holistic approach encompassing fatigue testing, crack measurement, and computational prediction of crack growth rates. During fatigue testing, crack shapes and growth are quantified using a novel surface replication technique that is applied to investigate crack nucleation, as well as to collect validation data that includes an accurate description of crack shape during crack propagation, a challenging and essential component in predicting crack growth. Computational simulation of fatigue crack growth in non-straight, complex surface crack arrays typically requires high fidelity analysis using computationally expensive methods to account for the mathematical and geometrical complexities inherent in the solution. A dislocation distribution based technique has been previously demonstrated to rapidly and accurately predict the stress intensity factors for through cracks of complex shape. This method was expanded and investigated as an approach for rapidly predicting the crack growth rate of kinked and tortuous surface crack arrays, using the crack configuration and bulk material properties as inputs. To investigate the accuracy and effectiveness of this characterization approach, surface crack growth in AA7075-T7351 was experimentally analyzed and modeled under high cycle and low cycle fatigue conditions. This comprehensive approach was determined to be an expedient and applicable method for characterizing and evaluating the nucleation and crack growth rate of non-planar microstructurally small and short crack configurations.